Mademoiselle Fifi - Maupassant, Guy de, 1850-1893 (Salt Lake City, UT : Project Gutenberg, 2003)
"Mademoiselle Fifi" by Guy de Maupassant is a short story published in 1882. Set during the Franco-Prussian War, the story unfolds in a Norman chateau occupied by bored Prussian officers. To break their monotony, they host a raucous dinner party with local prostitutes. When the arrogant sub-lieutenant known as "Mademoiselle Fifi" makes one provocation too many, a Jewish prostitute named Rachel takes a dramatic stand that transforms her into an unlikely symbol of resistance against the German occupation. (This is an automatically generated summary.)
Mademoiselle Fifi -- Boule de Suif.
Wikipedia page about this book: https://en.wikipedia.org/wiki/Mademoiselle_Fifi_(short_story)
Release date is 2003-12-01
Typed by Brett Fishburne Proofed by Reina Hosier and Kestrel
Keywords: Short stories, French -- Translations into English